Gérer les dysfonctionnements. Les ingénieurs de l’assainissement à Varanasi (Inde) - Bérénice Girard (Tracés, 2018)
Urban infrastructures are often particularly visible in India, both due to their recurrent failures and to the rhythm of their construction. In this article, we look at the wastewater treatment system of Varanasi, which has become since the 1980s, a symbol of the difficulties of urban planning in contemporary India, as millions of litters of wastewater flow untreated into the river Ganges despite large investments (Alley, 2014). By focusing on the technical workers who operate and maintain these infrastructures, we try to decipher their vision and analysis of the situation and the role of social, professional and institutional dynamics in the perpetuation of failure.